Simultaneous Pancreas-Kidney transplant: Pancreatic Graft Failure in The First Year Post-Transplant : Cast Study - Nixon, Mickaela; Ceresa, Carlo (Journal of the Nuffield Department of Surgical Sciences, 2020)
Approximately 15% of the pancreas grafts transplanted simultaneously with a kidney in insulin-dependent diabetics fail within the first year.1–3 Aside from rendering the recipient insulin-dependent, this failure has the additional disadvantages of decreased patient and renal allograft survival.1 In this case report, the experiences of a patient with Type 1 diabetes who suffered pancreatic graft failure less than one month post simultaneous pancreas-kidney transplant are shared. Subsequently, the merits of the simultaneous transplant compared to other therapies are investigated, highlighting the importance of pancreatic graft function one-year post-transplant. Finally, research investigating the causes of early pancreatic graft failure is presented and discussed.